Sedation-Induced Burst Suppression Predicts Positive Outcome Following Traumatic Brain Injury - Frohlich, Joel; Johnson, Micah A.; McArthur, David L.; Lutkenhoff, Evan S.; Dell'Italia, John; Real, Courtney; Shrestha, Vikesh; Spivak, Norman M.; Ruiz Tejeda, Jesús E.; Vespa, Paul M.; Monti, Martin M. (Frontiers in Neurology, 2021)
While EEG burst-suppression is often induced therapeutically using sedatives in the ICU, there is hitherto no evidence with respect to its association to outcome in moderate-to-severe neurological patients. We examined the relationship between sedation-induced burst-suppression (SIBS) and outcome at hospital discharge and at 6-month follow up in patients surviving moderate-to-severe traumatic brain injury (TBI). For each of 32 patients recovering from coma after moderate to severe TBI, we measured the EEG burst suppression ratio (BSR) during periods of low responsiveness as assessed with the Glasgow Coma Scale (GCS). The maximum BSR was then used to predict the Glasgow Outcome Scale extended (GOSe) at discharge and at 6 months post-injury. A multi-model inference approach was used to assess the combination of predictors that best fit the outcome data. We found that BSR was positively associated with outcomes at 6 months (P = .022) but did not predict outcomes at discharge. A mediation analysis found no evidence that BSR mediates the effects of barbiturates or propofol on outcomes. Our results provide initial observational evidence that burst suppression may be neuroprotective in acute patients with TBI etiologies. SIBS may thus be useful in the ICU as a prognostic biomarker.